2019
DOI: 10.14202/vetworld.2019.459-465
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some parameters on the ability of Listeria monocytogenes, Listeria innocua, and Escherichia coli to form biofilms

Abstract: Aim: The present study was conducted to evaluate the capacity of Listeria monocytogenes (L.m), Listeria innocua (L.i), and Escherichia coli to form biofilms on polystyrene support under different parameters by performing crystal violet (CV) staining technique. Materials and Methods: Different suspensions were prepared with single strains and with multiple combinations of strains including two serogroups of L.m (IIa and IIb), L.i, and E. coli strains at different microbial load. Selected strains and combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This pattern has been previously documented in surfaces conditioned with P. fluorescens biofilms (Puga et al 2018). L. monocytogenes is a facultative microorganism capable of forming biofilms under oxygen restrictive conditions (Lezzoum-Atek et al 2019). The fact that L.…”
Section: Discussionsupporting
confidence: 56%
“…This pattern has been previously documented in surfaces conditioned with P. fluorescens biofilms (Puga et al 2018). L. monocytogenes is a facultative microorganism capable of forming biofilms under oxygen restrictive conditions (Lezzoum-Atek et al 2019). The fact that L.…”
Section: Discussionsupporting
confidence: 56%
“…Although studies reported lactobacilli biofilm/biosurfactant activities against pathogens [10-13], few authors evaluated the inhibition of the initial adhesion of pathogens [16,17,23,33]. Some studies previously characterized the inhibition of the initial adhesion of certain pathogens, such as Gardnerella vaginalis, Prevotella bivia, Mobiluncus mulieris [23], Listeria monocytogenes [34], and Streptococcus mutans [17]. Recently, He et al [35] evaluated the probiotic activities of Lactobacillus species on the inhibition of the initial adhesion of several pathogens.…”
Section: Discussionmentioning
confidence: 99%